Analisis E-Service Quality, Kepercayaan dan Kenyamanan terhadap Loyalitas Pelanggan E-Commerce Marketplace Facebook - Shiddiq, Andy Ahmad; Yani, Muhammad (Ekonomis: Journal of Economics and Business, 2026)
The purpose of this study is to analyze the influence of e-service quality, trust, and convenience on customer loyalty of Facebook e-commerce marketplace. The population used is Facebook marketplace users in Sidoarjo City who have made purchases more than twice. Based on the calculation results, the sample in this study amounted to 96 participants. The analysis technique used the SmartPLS application. The results of this study prove that e-service quality, trust, and consumer loyalty have a significant effect on customer loyalty of Facebook e-commerce marketplace in Sidoarjo City.